2019
DOI: 10.1159/000501673
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Correlates of the Four-Way Laryngeal Contrast in Marathi

Abstract: The study examines acoustic correlates of the four-way laryngeal contrast in Marathi, focusing on temporal parameters, voice quality, and onset f0. Acoustic correlates of the laryngeal contrast were investigated in the speech of 33 native speakers of Marathi, recorded in Mumbai, India, producing a word list containing six sets of words minimally contrastive in terms of laryngeal specification of word-initial velar stops. Measurements were made for the duration of prevoicing, release, and voicing during release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 62 publications
2
9
0
Order By: Relevance
“…Voiceless aspirated stops were characterized by the highest H1*-H2*, H1*-A1*, H1*-A2*, and H1*-A3* onsets compared to other two laryngeal categories. These results are in line with other languages of the world where aspirated stops have been shown as having a higher spectral tilt at the onset of the following vowels than unaspirated stops (Shanghai Chinese: Gao et al 2020;Yerevan Armenian: Seyfarth and Garellek 2018;Dzongkha: Kirby and Hyslop 2019;Hindi/Urdu: Schertz and Khan 2020;Gujarati: Esposito et al 2020;Marathi: Berkson 2019;Dmitrieva and Dutta 2020). Raising of the spectral tilt due to aspiration appears to be a universal correlate.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Voiceless aspirated stops were characterized by the highest H1*-H2*, H1*-A1*, H1*-A2*, and H1*-A3* onsets compared to other two laryngeal categories. These results are in line with other languages of the world where aspirated stops have been shown as having a higher spectral tilt at the onset of the following vowels than unaspirated stops (Shanghai Chinese: Gao et al 2020;Yerevan Armenian: Seyfarth and Garellek 2018;Dzongkha: Kirby and Hyslop 2019;Hindi/Urdu: Schertz and Khan 2020;Gujarati: Esposito et al 2020;Marathi: Berkson 2019;Dmitrieva and Dutta 2020). Raising of the spectral tilt due to aspiration appears to be a universal correlate.…”
Section: Discussionsupporting
confidence: 87%
“…3 Some studies have also observed the effect of aspiration on F0 onsets but there appears to be inconsistency in the reported results. Voiceless unaspirated stops of Burushaski (Hussain 2021), Cantonese, Mandarin (Luo et al 2016), Kalasha (Hussain and Mielke 2020), Marathi (Dmitrieva and Dutta 2020), and Shanghai Chinese (Chen 2011) showed higher F0 onsets than voiceless aspirated stops. In contrast, voiceless unaspirated stops of Chru (Brunelle et al 2020), Madurese (Misnadin 2016), and Thai (Shimizu 1989) entailed lower F0 onsets than voiceless aspirated stops.…”
Section: Acoustic Correlates Of Laryngeal Contrastsmentioning
confidence: 93%
See 1 more Smart Citation
“…From prior examination of aspirated tokens (see Section 1.2), we assume that voice quality cannot be reliably characterized on aspiration because phonation is most often absent. However, we expect that phonation adjacent to the aspiration interval may be relatively breathy in Yemba, in line with previous experimental findings showing carryover coarticulation of laryngeal state from onset consonants to following vowels (Löfqvist & McGowan 1992;Ní Chasaide & Gobl 1993;Dutta 2007;Dmitrieva & Dutta 2020) and the initiation of glottal spread gestures prior to or during associated consonant constriction (Kagaya 1974;Kagaya & Hirose 1975;Benguerel & Bhatia 1980;Dixit 1989). In an effort to characterize the influence of aspiration on its surroundings and evaluate Hypothesis 2, we calculated voice quality measures from the EGG and acoustic signals for each flanking consonantal constriction and vowel.…”
Section: Methodssupporting
confidence: 89%
“…A positive VOT measurement occurs when vocal fold vibration follows the release of the oral closure. With respect to the voicing contrast, Dmitrieva and Dutta (2020) note that VOT 'has served as a cornerstone of acoustical investigations of laryngeal contrasts' and provides a unified basis for distinguishing stop voicing contrasts across a wide range of languages (p. 210). While VOT may serve as a primary or unifying cue, additional secondary cues may also be relevant, including F0 onset (Dmitrieva et al, 2015) and aspiration (Cho and Ladefoged, 1999).…”
Section: The Voicing Feature In English and Spanishmentioning
confidence: 99%